Human resettlement in lower Narmad basin. - "Varma, S.C." (Bhopal, 1985)
This book contains following topics: The Narmada river and its basin; The projects and their present status; Submergence in the lower Narmada basin; Policy parameters of human resettlement; The acquisition of land; Familywise survey in the area of submergence; In search of land for the oustees; Employment opportunities for the oustees; Fishery development; International experience in human resettlement operations.
Keywords: Dams India Madhaya PradeshNarmada